PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN APLIKASI QUIZIZZ TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA PADA MATERI AKU DAN LINGKUNGAN SEKITARKU - Iga Ghufrani Juniarti; Komariah; Yayang Furi Furnamasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Pancasila education in elementary schools faces the challenge of low student learning motivation. Initial data at SDN Mangunjaya 01 showed that 26.92% of fifth grade students had not achieved the KKM (Minimum Completion Criteria) on the material I and My Surrounding Environment. This study aims to analyze the effect of the Problem Based Learning (PBL) model assisted by the Quizizz application on the motivation and learning outcomes of fifth grade students in the Pancasila Education subject. The method used was a quasi-experiment with a Non-Equivalent Control Group Design. The sample consisted of 27 students in the experimental class (5A) and 27 students in the control class (5D) at SDN Mangunjaya 01. Data were collected through pretests and posttests, as well as learning motivation questionnaires. The results of the study showed that: (1) Student learning motivation in the experimental class increased significantly by 9.48 points (77.78% of students reached the high category), while in the control class it only increased by 2.08 points; (2) The cognitive learning outcomes of students in the experimental class increased by 25.37 points, while in the control class it was only 3.15 points; (3) There was a weak positive correlation between motivation and learning outcomes in the experimental class. These findings prove that the integration of PBL and Quizizz is effective in increasing student motivation and learning outcomes.